Examining Islamic Axiology: Santri’s Movement for Magrib Quranic Recitation Program - Lebba, Lebba (Universitas Hasanuddin, 2025)
The aim is to provide education and spiritual enlightenment for children that reciting Al-Qur'an regularly and with discipline at maghrib time and applying the values contained in it in everyday life is a spiritual consumption that can direct them to Islamic behavior. This research provides a scientific explanation of the benefits for santri to Recite Al-Qur’an at Maghrib time. The research data were obtained by interview and literature review. Research results show that the Santri Movement of Reciting Al-Qur’an at Maghrib time can form a generation with praiseworthy morals, good social spirit and always adhere to the regulation and teachings of Islam and prevent them from being addicted to the use of electronic devices. The implication, community could comprehend well the core of preaching.